(untitled) (SCIÉNDO INGENIUM, 2022)
Informality is a problem that encompasses many activities in our country, including economic activities, among them microenterprises, microentrepreneurs and workers do not comply with the laws established by the State through its authorities, either due to ignorance or Knowing them at least partially, they do not receive the benefit (s) when complying with them, thus generating a high labor and business informality, being estimated until 2019 on average throughout the country at 83.40 percent, in micro and small companies. Preferential taxes, financial leverage and a differentiated labor regime are part of public policies in order to reduce labor informality in micro-enterprises in Peru and their formalization, which is verified as not enough for this purpose, and must be articulated with others, including education, since it has been verified that the majority of workers and micro-entrepreneur employers do not have timely knowledge of the laws, that is, of the obligations and benefits when complying with them.